EXPLORING HOW GENDER MODERATES THE EFFECT OF PERSONALITY TRAITS ON OVERCONFIDENCE BIAS AMONG INVESTORS IN THE INDONESIAN STOCK MARKET - Natsir, Khairina; Arifin, Agus Zainul; Wijoyo, Fanny (Graduate Program of Universitas Tarumanagara, 2025)
This research aims to explore the impact of investor personality traits towards overconfidence bias in investment behaviors. Additionally, it examines whether gender differences serve as a moderating factor. The study focuses on three main variables: personality traits, gender, and overconfidence bias. Data for the study is gathered through a primary data collection method using an online questionnaire, distributed via Google Forms. This questionnaire incorporates relevant indicators that effectively represent the variables under investigation and is disseminated across social media platforms, including WhatsApp, Facebook, Instagram, Twitter, and Telegram, to broaden respondent reach. The sample consists of individual stock investors in Indonesia, selected through non-probability sampling. For statistical analysis, Structural Equation Modeling is employed using the SmartPLS software, applying the Partial Least Squares (PLS-SEM) approach based on variance. The evaluation includes an Outer Model Assessment (validity and reliability testing) and an Inner Model Assessment, which involves R-square, Q-square, and Goodness of Fit tests, alongside hypothesis testing. According to this study, neuroticism and conscientiousness positively contribute to overconfidence bias in both genders, while openness has a negative effect on this bias among male and female investors alike. The findings of this study imply that understanding investors' personality traits, such as neuroticism, conscientiousness, extraversion, and openness, is essential for tailoring investment strategies and mitigating overconfidence bias. Financial education focusing on self-awareness and emotional management is crucial to helping investors make more rational decisions and avoid unnecessary risks.